Some Observations On Turbulent Deposition Rates Of Coal Dust In Mine Airways - R. Bhaskar (Society for Mining, Metallurgy & Exploration, 1995)
Although the health effects of airborne dust in underground coal mines are well recognized, a lack of understanding remains about the fundamental mechanisms of dust generation, transportation, deposition and dust-lung reaction. This study was intended to contribute to the understanding of dust transportation and deposition mechanisms in underground mine airways. Data from in-mine experiments carried out under controlled conditions in a straight section of a longwall panel with three different airflow velocities and two different types of coal dust (bituminous and semi-anthracite) were used to determine the turbulent deposition rate of dust particles. Measurements of ambient dust concentrations and deposition along the mine airway were obtained and the total dust deposition velocity (rate) was calculated. The deposition velocity of turbulent diffusion was estimated based on the experimental data and theoretical equations. The effects of airflow velocity, particle size, particle density and distance from the dust source on gravitational, turbulent and total dust deposition are discussed along with related conclusions.